Possible Health Risk of Cellulose-Based Materials - Haziqatulhanis, Ibrahim; Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Rishen Nair, Krishnan (Springer, Singapore, 2022)
Cellulose-based products are currently receiving tremendous attention from researchers all over the world. It can be used in wide variety of applications including water treatment industry. However, there are scarce publications that touch on the possible risk that evolved from the usage of cellulose-based materials. This mini review aims to cover the respiratory risk possibility of nanocellulose by summarizing the findings by various researchers of their in vivo test. It was concluded that cautions need to be taken when handling the materials to prevent the exposure to higher risk.